2016
DOI: 10.1016/j.gene.2015.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell technologies in environmental omics

Abstract: Environmental studies are primarily done by culturing isolated microorganisms or by amplifying and sequencing conserved genes. Difficulties understanding the complexity of large numbers of various microorganisms in an environment led to the development of techniques to enrich specific microorganisms for upstream analysis, ultimately leading to single-cell isolation and analyses. We discuss the significance of single-cell technologies in omics studies with focus on metagenomics and metatranscriptomics. We propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…The throughput of microtiter plates has been enhanced through the incorporation of robotic technologies [104]. Also, fluorescence-activated cell sorting (FACS) has been used to distribute single cells into microtiter plates [105]. However, these kind of experiments require a strong prior knowledge on the best convenient substrates and also the chemistry on how it works.…”
Section: Microtiter Plate Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The throughput of microtiter plates has been enhanced through the incorporation of robotic technologies [104]. Also, fluorescence-activated cell sorting (FACS) has been used to distribute single cells into microtiter plates [105]. However, these kind of experiments require a strong prior knowledge on the best convenient substrates and also the chemistry on how it works.…”
Section: Microtiter Plate Screeningmentioning
confidence: 99%
“…FACS enables the selection of cells based on cell size, shape, and fluorescence [12], [59], [106], [107], [108]. FACS have many advantages: (1) it deposits single events into a variety of vessels quickly and accurately; (2) the laminar flow fluidics of FACS prevents disruption of cells during sorting; and (3) the contamination is limited because of the small volume of each droplet [105], [109], [110]. Due to its powerful sorting abilities, FACS is easily coupled to a number of different high-throughput screening methods such as droplet sorting and reporter-based screening.…”
Section: Facs-based Screeningmentioning
confidence: 99%
“…The future progress should obviously focus on extensive marine bioprospecting based on metagenomics approaches (Kodzius and Gojobori 2015). Sample heterogeneity is a major issue when dealing with environmental omics, and single cell techniques for reducing sample heterogeneity are arguably the best way forward (Kodzius and Gojobori 2016). These experimental approaches should be followed by comprehensive in silico comparison of metabolic features of local species compared to their counterparts from other environments.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that if metagenomics and SCGA methodologies are coupled with other "omics" technologies, such as transcriptomics, proteomics and metabolomics (i.e. study and quantification of mRNA transcript levels, proteins and cellular metabolites respectively), it could lead to further development of scientific capabilities for harnessing the genetic and metabolic potential of the extremophilic microbial diversity [30,31].…”
Section: Introductionmentioning
confidence: 99%